Rational design of an epitope-centric vaccine against Pseudomonas aeruginosa using pangenomic insights and immunoinformatics approach - Mudipalli Elavarasu, Santhosh; K, Sasikumar (Frontiers in Immunology, 2025)
IntroductionAs a highly adaptable opportunistic pathogen, Pseudomonas aeruginosa presents a significant threat to people with weakened immune systems. This is because it naturally resists antibiotics and can form biofilms. These factors complicate treatment and underscore the urgent need for innovative therapeutic strategies, such as vaccines, to combat this pathogen.MethodsA pangenome analysis of P. aeruginosa genomes was performed to identify conserved core genes critical for bacterial survival and virulence. LptF, an outer membrane protein, was prioritized as a target for vaccine development. B-cell and T-cell epitopes were predicted from LptF using immunoinformatics tools, and a multi-epitope peptide vaccine was designed. The interaction between the vaccine candidate and Toll-like receptors (TLRs) was investigated through molecular docking and molecular dynamics simulations. Codon optimization and in-silico cloning were carried out to validate the vaccine’s expression potential in E. coli. Immune response simulations evaluated the vaccine’s immunogenicity.ResultsOur pangenome analysis identified highly conserved core genes, including LptF, which proved crucial for bacterial virulence. A multi-epitope peptide vaccine was designed using the most immunogenic B-cell and T-cell epitopes derived from LptF. Studies using molecular docking and dynamic simulation have shown stable interactions between the vaccine and TLRs, with the POA_V_RS09 construct exhibiting the highest stability. Codon optimization indicated high expression efficiency in E. coli. Immune simulations revealed robust adaptive immune responses, including sustained IgG production, the formation of memory B cells, and the activation of T-cell responses.DiscussionThe POA_V_RS09 vaccine candidate exhibited excellent stability, immunogenic potential, and expression efficiency, making it a promising candidate for combating P. aeruginosa infections. This study provides a strong foundation for developing effective therapeutic strategies to address the growing issue of antimicrobial resistance in P. aeruginosa. More experimental validation is needed to verify its effectiveness in preclinical and clinical environments.